Acute generalized exanthematous pustulosis due to hydroxychloroquine after a prolonged latent period. Issue 1 (20th April 2018) - Kaneko, Takahide; Takiyoshi, Noriko; Fukui, Tomohisa; Hagiwara‐Sagara, Chihiro; Nakano, Hajime; Sawamura, Daisuke
Abstract : We report a case, that is, to our knowledge, the first case of HCQ‐induced AGEP in Japan. Our case required a longer time for complete resolution of the condition because of the waxing and waning "smoldering eruption" during the clinical course. It is possible that HCQ‐induced AGEP is unique in its clinical course, unlike AGEP due to other drugs.